Nanosensors: Localized Synthesis of Iron Oxide Nanowires and Fabrication of High Performance Nanosensors Based on a Single Fe2O3 Nanowire (Small 16/2017). Issue 16 (19th April 2017) - Lupan, Oleg; Postica, Vasile; Wolff, Niklas; Polonskyi, Oleksandr; Duppel, Viola; Kaidas, Victor; Lazari, Eugen; Ababii, Nicolai; Faupel, Franz; Kienle, Lorenz; Adelung, Rainer
Abstract : In article number1602868, by Oleg Lupan, Franz Faupel, Lorenz Kienle, Rainer Adelung, and co‐workers, localized synthesis of iron oxide nanowire networks directly on a device structure by thermal oxidation at relatively low temperatures (255 °C) is successfully reported. Nanosensors based on a single Fe2 O3 nanowire with different diameters down to 25 nm are fabricated and show excellent acetone sensing properties at room temperature.